Formulasi Sediaan Minuman Serbuk Fungsional Kombinasi Biji Jagung (Zea mays L. ) dan Madu - Utami, Sheila Meitania; Ismaya, Nurwulan Adi; Ratnaningtyas, Tri Okta; Yunarto, Nanang (Jurnal Kefarmasian Indonesia, 2022)
Corn is a food ingredient that contains carotenoids that are very potential in preventing cancer, adding endurance, as antivirals, fungi, and parasites, carotenoids are also good for vision, growth and reproduction. The highest carotenoid compound in corn is lutein which has potential as an immunomodulator. Honey is also immunomodulatory by triggering macrophages to produce cytokines involved in killing bacteria and tissue repair. The combination of corn and honey in one drink will produce a health supplement preparation that contains antioxidants and immunomodulators that are good for health. The goal of this study was to get the best formula of instant granules physically. Instant granules are made from corn kernels that have been dried with a combination of honey which is processed by dry granulation with variations of corn kernels FI & FIV (15%), FII & FV (25%), FIII & FVI (35%), and FI & FIV honey (35%), FII & FV (25%), FIII & FVI (15%). Instant granules are conducted physical test evaluations including organoleptic tests, flow time, angle of repose, compressibility index, time of granules to dissolve, particle distribution, pH, viscosity of reconstituted and RDA test. The results showed that the granule flow time, angle of repose, compressibility index, time of granules to dissolve, granules particle distribution and viscosity of reconstituted overall physical testing showed no noticeable differences, except against the most preferred taste parameters FVI. So the best formulation has obtained is FVI and shows the result of the RDA test with total energy of 350 kcal/100 grams.